The MESSIER surveyor: unveiling the ultra-low surface brightness universe. Issue Volume 11:Issue S321(2015) (21st March 2017) - Valls-Gabaud, David; ,
Abstract: The MESSIER surveyor is a small mission designed at exploring the very low surface brightness universe. The satellite will drift-scan the entire sky in 6 filters covering the 200–1000 nm range, reaching unprecedented surface brightness levels of 34 and 37 mag arcsec −2 in the optical and UV, respectively. These levels are required to achieve the two main science goals of the mission: to critically test the ΛCDM paradigm of structure formation through (1) the detection and characterisation of ultra-faint dwarf galaxies, which are predicted to be extremely abundant around normal galaxies, but which remain elusive; and (2) tracing the cosmic web, which feeds dark matter and baryons into galactic haloes, and which may contain the reservoir of missing baryons at low redshifts. A large number of science cases, ranging from stellar mass loss episodes to intracluster light through fluctuations in the cosmological UV-optical background radiation are free by-products of the full-sky maps produced.